A psicanálise do olhar: do ver ao perder de vista nos sonhos, na pulsão escópica e na técnica psicanalítica - Liliane Camargos (2008)
The universality of themes and discussions is impressive, that Psychoanalysis of Sight is capable of provoke. In this study, this amplitude needed to be restricted to some parameters that could answer to the three main questions that form its argumentativeaxle: How do blind people dream? Does a blind person have a scopic drive? What is the function of the couch for the analytical technique when the analyst or the patient is blind? To answer them, hypotheses have been raised that justify the marked presence of sight in all of these aspects, and proposals of applicability have been created of thetheoretical concepts and in practice, such as in cases of people for whom vision and the visual perceptive memory are absent. Thus, focused sight as perception, tool, something constituent of the psyche or even as metaphor, will be analyzed in the theory of dreams and its interpretation, the theory of scopic drive and the psychoanalytic technique.